Kreativitas Desain Poster dalam Kompetisi Desain Poster Nasional - Ahmad, Arif Priyono Susilo (Bina Nusantara University, 2012)
Poster design competition/contest has become quite often held in Indonesia. Themes and organizers are varied, ranging from educational institutions, government, commercial and social institutions. On the one hand, the rise of this activity can be a trigger for the creativity of the nation, but on the other hand certainly it can cause turmoil in terms of the lack of exploration of ideas and applications. Too much information often overrides the hierarchy of information. Visual elements in a poster design contest overlap, compete for the attention of the viewers, so that we neglect the functions of persuasion. The functions of promotion poster is to communicate everything relating to the contest, including the contest theme, subtheme, explanations and background of the contest, organizers, prizes, attendees can participate, size and amount of work, limitations of work, deadlines, details of the jury, the address and number contest material delivery phone, website or email or phone number the committee can be contacted, and so on. Terms and conditions of the contest should be clearly communicated to the public. Poster contest that contains all of the terms and conditions of the competition will just be a communication medium and severe fatigue with too much text. Promotional poster contest should be able to convey a clear message and information about the contest, as well as be able to inspire and motivate potential competitors, so that the aim to capture ideas and a great poster design can be achieved. For this reason, the poster campaign of the poster competition must appear charming, unique, inspiring, creative, and nuanced in line with the theme.